Study of Tensile Strength Test of Oxi-Asetyline Welding with the Addition of Borax to St 37 Steel - Bagas Ariya Dipangga; Prantasi Harmi Tjahjanti (Procedia of Engineering and Life Science, 2021)
The use of welding in industry today is very broad, including shipping, machinery, construction and others. The aim of this research was to study the welding results of two types of metal with different melting points, namely low carbon steel ST37 with brass filler and borax added during the welding process using OAW (Oxygent Acetyline Welding) welding. The specimen size is 170 mm long, 50 mm wide and 8 mm thick. As for the test method with the addition of borax, then look at the results of the number of porosity, weld defects and differences in tensile strength in each specimen by conducting penetrant liquid testing and tensile testing with ASTM E-8 standards. The results of the penetrant liquid test showed that welding ST 37 steel using borax as an additional material produced welding with the smallest porosity and even no defects at all compared to specimens without using borax. The results of the tensile test show that the addition of borax has a tensile strength value of 2000 kgf / mm². This value is greater than without the addition of borax.